HBSP improves kidney ischemia-reperfusion injury and promotes repair in properdin deficient mice via enhancing phagocytosis of tubular epithelial cells - Wu, Yuanyuan; Huang, Lili; Sai, Wenli; Chen, Fei; Liu, Yu; Han, Cheng; Barker, Joanna M.; Zwaini, Zinah D.; Lowe, Mark P.; Brunskill, Nigel J.; Yang, Bin (Frontiers in Immunology, 2023)
Phagocytosis plays vital roles in injury and repair, while its regulation by properdin and innate repair receptor, a heterodimer receptor of erythropoietin receptor (EPOR)/β common receptor (βcR), in renal ischaemia-reperfusion (IR) remains unclear. Properdin, a pattern recognition molecule, facilitates phagocytosis by opsonizing damaged cells. Our previous study showed that the phagocytic function of tubular epithelial cells isolated from properdin knockout (PKO) mouse kidneys was compromised, with upregulated EPOR in IR kidneys that was further raised by PKO at repair phase. Here, helix B surface peptide (HBSP), derived from EPO only recognizing EPOR/βcR, ameliorated IR-induced functional and structural damage in both PKO and wild-type (WT) mice. In particular, HBSP treatment led to less cell apoptosis and F4/80+ macrophage infiltration in the interstitium of PKO IR kidneys compared to the WT control. In addition, the expression of EPOR/βcR was increased by IR in WT kidneys, and furthered increased in IR PKO kidneys, but greatly reduced by HBSP in the IR kidneys of PKO mice. HBSP also increased PCNA expression in IR kidneys of both genotypes. Moreover, iridium-labelled HBSP (HBSP-Ir) was localized mainly in the tubular epithelia after 17-h renal IR in WT mice. HBSP-Ir also anchored to mouse kidney epithelial (TCMK-1) cells treated by H2O2. Both EPOR and EPOR/βcR were significantly increased by H2O2 treatment, while further increased EPOR was showed in cells transfected with small interfering RNA (siRNA) targeting properdin, but a lower level of EPOR was seen in EPOR siRNA and HBSP-treated cells. The number of early apoptotic cells was increased by EPOR siRNA in H2O2-treated TCMK-1, but markedly reversed by HBSP. The phagocytic function of TCMK-1 cells assessed by uptake fluorescence-labelled E.coli was enhanced by HBSP dose-dependently. Our data demonstrate for the first time that HBSP improves the phagocytic function of tubular epithelial cells and kidney repair post IR injury, via upregulated EPOR/βcR triggered by both IR and properdin deficiency.